1998
DOI: 10.1046/j.1365-2842.1998.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bacterial adherence onto pellicle‐coated aesthetic restorative materials

Abstract: Adhesion of oral bacteria to teeth and restorative materials plays an important role in the pathogenesis of oral diseases. This study investigated the initial adhesion of Streptococcus mutans to enamel and restorative materials. Three types of composites and two types of glass ionomer cements were used. The specimens were coated with freshly collected human parotid saliva. The salivary coated samples were incubated with cell-free glucosyltransferase, and further incubated with sucrose solution. Finally, the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 19 publications
2
23
1
Order By: Relevance
“…4 Adhesion of bacteria to rough surfaces in the oral cavity is mediated by different mechanisms, involving the type of the bacterial species and the surface itself. 29 The results of the present study refuted the first hypothesis of the study and showed that the type of the restorative material signifi cantly affected the surface hardness, and giomer samples exhibited more SR. In the present study, a profi lometer was used to determine SR, which is an accurate and appropriate technique.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…4 Adhesion of bacteria to rough surfaces in the oral cavity is mediated by different mechanisms, involving the type of the bacterial species and the surface itself. 29 The results of the present study refuted the first hypothesis of the study and showed that the type of the restorative material signifi cantly affected the surface hardness, and giomer samples exhibited more SR. In the present study, a profi lometer was used to determine SR, which is an accurate and appropriate technique.…”
Section: Discussionsupporting
confidence: 84%
“…Bleaching might also affect the chemical composition of the surface enamel and restorative materials, changing the adhesion process. 29 Bleaching might result in a decrease in the adhesion of salivary proteins on the surface of bleached materials through factors containing peroxide, and it appears it might affect the adhesion of cariogenic bacteria, such as S. mutans and S. sobrinus. 36 Gurgan et al 42 reported an antibacterial effect for 10% carbamide peroxide, consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The production of glucans promotes accumulation of S. mutans and strong adherence to solid surfaces 23,24) . In the present study, the water-insoluble glucans must have protected the formed biofilms even after vigorous shaking 25,26) . Perhaps, the current condition for FAAO incorporation into coating materials is not directly applicable for clinical applications.…”
Section: Discussionmentioning
confidence: 80%
“…After corrosion, the rough surfaces increased the bacterial adhesion [34]. Previous research [35] measuring the surface contact angles on metal surfaces indicated that acid-treated surfaces exhibit increased contact angles and more hydrophobicity with increasing surface roughness.…”
Section: Groupsmentioning
confidence: 94%